2010
DOI: 10.1352/1944-7558-48.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in Informed Consent Response on the Basis of Demographic Factors: Brief Report

Abstract: During an outcomes study of spasticity treatment at a developmental center for 62 residents with profound intellectual disabilities, either botulinum toxin A (BTX-A), intrathecal baclofen (ITB), or both were recommended with physical and occupational therapy. Conservators consented to BTX-A more than ITB (p = .021). Court-appointed conservators were more likely to provide consent for treatment than family members (p = .026). Nonparents consented more than parents (p = .009). Finally, Caucasian conservators wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This problem can raise issues because some studies have shown that non-parents are more likely to consent to have children participate in trials than parents. 21 What should be obtained in such situations is not yet clearly defined in many settings, leaving a gray area that needs to be explored further. Sponsors are encouraged to accept what is culturally acceptable to the community, and the local study team has to put mechanisms in place to ensure that the rights of the children are not infringed.…”
Section: Impact Of Clinical Trials On the Communitymentioning
confidence: 99%
“…This problem can raise issues because some studies have shown that non-parents are more likely to consent to have children participate in trials than parents. 21 What should be obtained in such situations is not yet clearly defined in many settings, leaving a gray area that needs to be explored further. Sponsors are encouraged to accept what is culturally acceptable to the community, and the local study team has to put mechanisms in place to ensure that the rights of the children are not infringed.…”
Section: Impact Of Clinical Trials On the Communitymentioning
confidence: 99%
“…To avoid having rumors disrupt activities, ongoing dialogue with the participants and communities is key. Having a community liaison officer who can monitor rumors is an asset [ 14 ]. It was important for the trial team to be aware of rumors quickly so that the rumor could be addressed in a timely manner.…”
Section: Rumor Management and Recruitmentmentioning
confidence: 99%
“…The child belongs to the family, so almost any adult could take care of the child and hence decide on behalf of the child. Documented legal guardianship is important however, as some studies have documented that guardians are more willing to allow participation in trials of children other than their own [ 14 , 15 ]. With infant trials it was easier to identify a parent, but with older children care had to be taken to establish who a legal guardian was.…”
Section: Consent and Subject Participationmentioning
confidence: 99%